Crescimento e características da carcaça de cordeiros Texel terminados em confinamento - Zago, Luana Côrtes (2013)
The aim of this study was to evaluate the growth of post-weaning feedlot Texel lambs. Were used a total of 30 non castrated male lambs, born of simple birth. The lambs were weaned at approximately 50 days of age, individually confined and distributed to five treatments with six replications, which each treatment had a predetermined slaughter weight (T23 - initial slaughter, T25, T30, T35 and T40). The diet consisted of sorghum (Sorghum bicolor (L) Moench) and concentrate mixing ground corn (Zea mays L.), soybean (Glycine max L.), and minerals. In the period preceding slaughter the lambs were weighed and performed the measurements in vivo. After bleeding, each non-carcass component was weighed individually. Subsequently, the carcasses were placed in cold storage at 2°C for 24 h and after this period, was performed an evaluation of these and each cut at right half carcass was weighed and individually frozen to perform dissection of tissues. The average daily weight gain was not affected by the increase in live weight at slaughter, yielding an average of 0.252 kg/day. There was a linear increase to conformation, to body condition score, to biometric measurements performed in vivo and also to all measurements of the animals carcass. The hot carcass weight and cold carcass weight increased linearly as a consequence of the increased slaughter weight of lambs. However, the hot carcass yield, cold carcass yield and cooling loss index were not influenced by slaughter weight, with mean values of 46.12%, 44.83% and 2.79%, respectively. Higher slaughter weight of lambs led to increase linearly the weights of neck, shoulder, ribs and leg, regarding the regional composition of the carcass. When expressed in percentage terms, only the percentage of leg was influenced by slaughter weight, with a linear decrease. The results for the relative growth or allometric indicate that the shoulder and leg show early development, while the neck and ribs have delayed development. The weights of tissues bone, muscle and adipose increased linearly in the half-carcass and its regions. However, the percentage of bone in the neck remained constant and decreased linearly in other cuts, the muscle decreased only in ribs and remained constant in other cuts and fat increased linearly in all of them, indicating that the heavier is the animal, greater is the proportion of fat in the carcass. The allometric coefficients indicate that bone tissue and muscle are early growth, while the fat is delayed in both commercial cuts and the carcass as a whole. The relation muscle/fat decreased in all cuts and muscle/bone relation increased linearly in all of them except the neck which remained constant. The results for non-carcass components indicate that most of animals got an increment of weight as the increase of live weight. Observing their percentages, most were not influenced by live weight, only the constituents lungs + trachea, abomasum, small intestine, large intestine, head and feet decreased proportionately according to the increase of lambs slaughter weight. The body parts liver, diaphragm, rumen, reticulum, omasum, skin, tongue, testicles, kidney fat and internal fat have delayed development. Conversely, lungs+trachea, esophagus, heart, pancreas, kidneys, spleen, abomasum, small intestine, large intestine, blood, head, feet, and penis are body components that present early development.